Trafficking In Women and Children in Yorubaland: The Pre- Colonial, Colonial and Post Colonial Situations Compared (Global Journal of Human-Social Science, 2012)
Trafficking in human beings is today a global phenomenon with global consequences Within trafficking in human beings are specifics such as women trafficking children trafficking and women and children trafficking Although trafficking in women and children is going to be the subject matter of this paper trafficking in human being generally is an old phenomenon with a positive effect until it became abused from the pre-colonial days to now Culturally some aspects of Yoruba people s culture are consistent with it Unlike the position of the United Nations which prohibits extracting labor from women and children under certain age the Yoruba culture encourages it A Yoruba proverb atikekere laa ti pee kan iroko to ba dagba tan apa ko nii kaa mo children are better caught and molded when they are young or else it would be difficult to do so when they are grown up tells us why The Yoruba believe in the virtue of training children from tender ages in some forms of trade and craft However the noble cultural intention of catching and molding children at tender age has been given a dehumanizing tar by modern day trafficking in women and children locally and internationally This paper intends to examine trafficking in women and children in the pre-colonial colonial and post colonial periods with the aim of establishing and understanding the motivational nexus of the operators of these illegal trades across the ages